RELATIONSHIP BETWEEN ADHERENCE TO TAKING ANTIRETROVIRAL DRUGS AND NUTRITION INTAKE WITH THE QUALITY OF LIFE OF PERSON WITH HIV (PLHIV) AT JOHAR BARU PUBLIC HEALTH CENTER (Proceedings OPTIMAL, 2025)
Human Immunodeficiency Virus (HIV) is a virus that can weaken the immune system. When the immune system weakens, the body becomes more susceptible to various pathogens, which can ultimately cause AIDS (Novita, 2022). In general, someone who is confirmed positive for HIV is called PLHIV (People with HIV). The aim of this research is to determine the relationship between medication adherence and nutritional intake on the quality of life of PLHIV. The number of respondents who met the inclusion criteria were aged 30-49 years and were married. Observations were made when patients took ARV drugs in June 2024, the majority of respondents had high compliance with ARV drug consumption (45.70%), good quality of life (68.6%), adequate nutritional intake. The results of the Somers'd test showed a significant relationship between adherence to taking medication and the nutritional status of respondents (0.002) with a level of closeness that was close to perfect and quality of life (0.007) with a strong relationship. However, there was no significant relationship between nutritional intake and the nutritional status and quality of life of respondents (p>0.005). This research concludes that the level of medication adherence can be related to the quality of life of PLHIV. It is recommended that health workers provide education to PLHIV regarding vitamin C and zinc by increasing consumption of vegetables and fruit.